(untitled) (Global Journal of Medical Research, 2020)
Introduction: Hemolytic uremic syndrome in postpartum is an orphan disease, characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. It occurs due to abnormal complement activation, which activates the membrane attack complex. Pregnancy is characterized by being a pro inflammatory state, which has been related as one of the possible triggers for this pathology. According to its pathophysiology, the use of "Eculizumab" has been established as a gold standard treatment in this pathology. This is a humanized IgG2 monoclonal antibody that blocks the conversion of C5 to C5a, with subsequent inhibition in the formation of the membrane attack complex.